IDENTIFICATION OF MULTIDRUG RESISTANT ESCHERICHIA COLI FROM THE DRINKERS OF BROILER CHICKEN POULTRY STATIONS LOCATED ACROSS THE VIRUDHUNAGAR DISTRICT, TAMIL NADU, INDIA - SUNDARAMAHALINGAM, BALAJI; SANTHILAL, CHANDAN; MARIMUTHU, NARAYANAN (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objectives: The present investigation aimed to identify the multidrug resistance Escherichia coli bacteria in drinkers of poultry stations located across the Virudhunagar district, Tamil Nadu, India. Because water is the most important part of digestion in the growing chicks of poultry stations, but the quality of water supplied is often negotiated and the water drinkers in poultry farms has becoming the heavenly ground for antibiotic resistance (ABR) generation. Methods: Hence in the present investigation water samples from the drinkers of five poultry stations were collected and analyzed for E. coli resistance bacteria using the disk diffusion method of Bauer–Kirby technique. Results: Screening for ABR against the disc of penicillin, ampicillin, chloramphenicol, streptomycin, kanamycin, and cephalosporin were performed. Among the water samples collected from drinkers of five sampling sites, three sampling sites were found to show resistance bacteria against the different antibacterial disc used. Conclusion: To overcome the development of ABR bacterial strains from poultry stations point of use disinfectant techniques rather than using chlorine and other chemical disinfectants can be developed to alleviate this problem.